2016
DOI: 10.1093/ecco-jcc/jjw053
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Anti-TNF Therapy in Inflammatory Bowel Disease

Abstract: Several anti-tumour necrosis factor [TNF] blocking strategies have been evaluated in patients with Crohn's disease. Compounds that have been tested included the full monoclonal IgG1 antibodies infliximab and adalimumab, the pegylated anti-TNF F[ab']2 fragment certolizumab, an IgG4 anti-TNF CDP571 with reduced affinity for the Fc receptor, the soluble TNF receptor I onercept, and the TNF receptor II-Fc fusion protein etanercept. The endpoints of these studies suggest that not all methods of blocking TNF are equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(188 citation statements)
references
References 67 publications
6
176
0
6
Order By: Relevance
“…Corticosteroids are known to induce apoptosis in lymphocytes but not neutrophils [14] and to induce demargination of neutrophils from the endovascular lining. Similarly, infliximab functions by inducing apoptosis of activated T-lymphocytes through transmembrane TNFα, in addition to inhibiting soluble TNFα [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids are known to induce apoptosis in lymphocytes but not neutrophils [14] and to induce demargination of neutrophils from the endovascular lining. Similarly, infliximab functions by inducing apoptosis of activated T-lymphocytes through transmembrane TNFα, in addition to inhibiting soluble TNFα [15]. …”
Section: Introductionmentioning
confidence: 99%
“…45,46 By contrast, Wojtal et al 47 has suggested that the Fc receptor CD64 could be connected to reduced responsiveness to IFX in IBD. The study detected increased expression of interferon γ (IFN-γ) in the inflamed colonic tissue from nonresponders, which could lead to increased transcription of the CD64 gene.…”
Section: The Role Of Fc Receptorsmentioning
confidence: 98%
“…These substances induce apoptosis of CD4 + -T-cells and macrophages and influence the cytokine milieu by binding to soluble and membrane-bound TNF [42]. Due to the lack of an Fc region in certolizumab, some effects are only observed with adalimumab and infliximab [43]. …”
Section: Approved Substances – State Of the Artmentioning
confidence: 99%